PERILAKU MASYARAKAT DESA PANGKUNGKARUNG KERAMBITAN KABUPATEN TABANAN TERHADAP PENCARIAN PENGOBATAN GIGI TAHUN 2012 - I Made Ariyasa Putra; Ni Ketut Ratmini (Jurnal Kesehatan Gigi (Dental Health Journal), 2013)
Dental treatment search behavior have tight correlation with community perception for disease, knowledge, attitude, income,and dentist. The purpose of this study was to determine description of community behavior  Pangkungkarung village Kerambitan Tabanan regency of dental treatment search in 2012. The research was conducted with a cross sectional  method with interviews of 50 respondents.The results showed a majority (38%) of respondents who experience toothache  choose to seek treatment for dental practice. Based on the level of education, the search for  dental treatment by a high school education level of respondents  who  mostly (80%) choose dental practice. Based on the type of work ,respondents  who  work as  employees  mostly (56,6%) choose dental practice. Based on the analysis of these data, it can be concluded mayority respondents who experience toothache choose  dental practice to seek  treatments based high school education level or type work as employees.After that,medicine center health proposed to equip a good health instrument, so that there were a favorite place for community choose to seek treatment.